História da educação infantil em Foz do Iguaçu: uma análise a partir da legislação (1976-2000) - Santos, Deisiane Leite da Silva (2023)
Through this research, we seek to historicize the trajectory of Early Childhood Education (EI) at a national and state level with an emphasis on the Western region of Paraná - as this is where the highlighted municipality is located, and finally, the municipality of Foz do Iguaçu/PR . In Brazil, the trajectory of EI began following European models, but was modified to adapt to the specific characteristics of each region. In this sense, the municipality of Foz do Iguaçu/PR created the first educational institutions, but there are still no published works that address the implementation of Early Childhood Education. Therefore, this research aimed to identify the documentary sources that historically based ECE in the municipality, highlight its social and political economic determinants, contribute to the understanding of the initiation and consolidation of ECE and discuss the historical development of this stage of basic education in Foz do Iguaçu/PR during the years 1976 and 2000. The present research is justified by the gap regarding the topic, given the absence of studies on the object of study within the temporal and geographical area presented. Furthermore, they have a personal justification, as the author is a public servant in the municipal education network in the city, as a Early Childhood Education teacher. Aiming to answer how the historical constitution of Early Childhood Education occurred in Foz do Iguaçu/PR, such as research in archives such as: documents from the Municipal Early Childhood Education Centers (Pedagogical Political Project), personal files, municipal library, survey of scientific production in Libraries Theses and Dissertations and Google Scholar. Given the results obtained, we concluded that EI is supported by local legislation, as there was no tradition of preserving or archiving physical documents in public offices and educational institutions. The historical context of EI in the municipality does not differ significantly from the national, state and regional context, standing out only for local particularities and specificities